The relationship between negative symptoms and cognitive functioning in patients at clinical high risk for psychosis. (October 2018) - Leanza, Letizia; Egloff, Laura; Studerus, Erich; Andreou, Christina; Heitz, Ulrike; Ittig, Sarah; Beck, Katharina; Uttinger, Martina; Riecher-Rössler, Anita
Highlights: Worse neurocognitive performance is associated with a higher level of negative symptoms. Measures of verbal fluency and nonverbal intelligence seem to be particularly associated with negative symptoms. The association between verbal fluency and alogia might suggest an overlap between the constructs. Abstract: Negative symptoms and neurocognitive performance have been reported to be negatively associated in patients with emerging psychosis. However, most previous studies focused on patients with frank psychosis and did not differentiate between subdomains of negative symptoms. Hence, we aimed to elucidate the specific relationship between negative symptoms and cognitive functioning in patients at clinical high risk (CHR) for psychosis. Data from 154 CHR patients collected within the prospective Früherkennung von Psychosen (FePsy) study were analyzed. Negative symptoms were assessed with the Scale for the Assessment of Negative Symptoms (SANS) and cognitive functioning with an extensive neuropsychological test battery. Regression analyses revealed significant negative associations between negative symptoms and cognitive functioning, particularly in the domains of nonverbal intelligence and verbal fluency. When analyzing each negative symptom domain separately, alogia and asociality/anhedonia were significantly negatively associated with nonverbal intelligence and alogia additionally with verbal fluency. Overall, our results in CHR patients are similar to those reported in patients with frank psychosis. The strong negative association between verbal fluency and negative symptoms may be indicative of an overlap between these constructs. Verbal fluency might have a strong influence on the clinical impression of negative symptoms (particularly alogia) and vice versa.